Synthesis of high surface area porous carbon from anaerobic digestate and it's electrochemical study as an electrode material for ultracapacitors - Chaturvedi, Vikash; Usangonvkar, Saurabh; Shelke, Manjusha V. (RSC Advances, 2019)
The remnants of the anaerobic digestion process, `the digestate,' mainly consist of fibrous lignin and cellulose like molecules, as a significant carbon repository along with some other inorganic impurities. The present work demonstrates the potential use of anaerobically treated fruit and vegetable waste (FVW) as a source of porous carbon for supercapacitor electrode materials. This work suggests that the FVW digestate can inherit silicon (Si) and calcium (Ca) based inorganic impurities, which play an essential role as structure directing agents for digestate derived carbon. These contaminants act as hard templates during carbonization to create hierarchical pores and contribute to an enhancement in surface area. Different batches from an anaerobic biogas digester plant are converted to porous carbon and examined as a potential supercapacitor electrode material. A maximum capacitance of 235 F g(-1) is achieved from DDHPC-4kh carbon with a specific surface area of 2502 m(2) g(-1) at a current density of 1 A g(-1) in an acidic aqueous electrolyte. The results are significant in comparison to other bio-sourced precursors studied previously.